Inflationary threshold effect on the nexus between economic growth and public debt: The case of Asian countries - Thanh, Huyen Nguyen; Thu, Trang Tran Thi; Thanh, Huyen Le (Asian Economic and Financial Review, 2024)
Our study is carried out in an attempt to investigate the causal relationship between economic growth and public debt under the influence of inflation in Asia. To achieve our research objectives, we used a threshold regression model and data collected from Asian countries from 2010 to 2021. The study results show that there is an inflation threshold of 10.4907% at which the influence of inflation changes and the increase in public debt harms the growth rate. Additionally, regression results on the relationship between public debt and economic growth show different results between developed and developing countries. The research results confirm previous researchers' theories and empirical findings on the relationship between inflation and economic growth. In addition, government spending negatively impacts economic growth, while population growth, capital stock, and trade scale positively impact economic growth. Studying the relationship between economic growth and public debt can provide a helpful reference for Asian policymakers. Accordingly, governments should pay special attention to maintaining moderate inflation and limiting public debt to promote economic growth.